Effect of agriculture waste materials application on Kenaf (Hibiscus cannabinus) growth and resistancy against root knot nematode disease - Norhayati, Ngah; Siti Nur Fatihah, Hashim; Az'wafa, Rozali; Mohammad Hailmi, Sajili; Tajul Afif, Abdullah; Abd Jamil, Zakaria; Salmah, Mohamed; Mohd Norsyam, Yahaya; Kamaruddin, Mokhtar (2021)
BRIS soil fertility and the infestation of root-knot nematode is the main challenge in Kenaf (Hibiscus cannabinus) plantation. The growth of kenaf is largely depended on the soil nutrient level and its resistancy against the infestation by pest and disease. This study was designed to determine the best soil treatment using agriculture waste materials for kenaf cultivation. The experiment conducted at 5 meter x 5 meter plot for each treatment by using Complete Randomized Design (CRD) and replicated 10 times. Soil were treated with biochar, cow dung, organic compost, and NPK fertilizer. The performance of those soil treatments were evaluated through the performance of plant growth and its physiological responses, as well as the plant resistancy against root-knot nematodes infestation. The results showed that kenaf grown at the field plot treated with cow dung has the better plant growth compared to the plants grown in other treatments. The application of cow dung was found significantly enhanced the height of the plant, chlorophyll content, stalk diameter, length of stalk, dry weight and fiber content of kenaf plant. In addition, the plant roots at the plot treated with cow dung is free from nematode infestation. As conclusion, cow dung is the best soil treatment as it is significantly produce the best result in plant growth performance, produce more fiber and free from root-knot nematode infestation.